On a Factorizable Group with Large Cyclic Subgroups in Factors - Chirik, I. K.; Чирик, И. К.; Чирик, И. К. (Institute of Mathematics, NAS of Ukraine, 2015)
We prove the supersolvability of a finite factorizable group $G = G_1 G_2 ...G_n$ with pairwise permutable factors each of which has a cyclic subgroup of odd order $H_i$ and $|G_i : H_i | ≤ 2$.